Pembekalan Keterampilan Servant Leadership Pada Mahasiswa Jurusan Administrasi Publik: Provision of Servant Leadership Skills for Students Majoring in Public Administration - Einsbie Grata Myn; Alivia Quroto A’yun (Cv. Utility Project Solution, 2023)
Students and female students of the Public Administration Study Program have never had technical skills in the form of public service practicum, so this service aims to make students and female students majoring in administration have public leader skills as servant leadership so that this ability can be utilized when entering the world of work. This method uses role-playing techniques in the form of sociodrama and psychodrama involving 25 students and female students majoring in public administration. The results achieved in this service are that some students like this practicum activity and get some learning from the ethics and procedures for serving and handling clients, customers and the community. Some of the students and female students still do not fully understand to manage the administrative files that have been completed, but on the other hand, the practice of communication and the procedures for delivering are quite good. recommendations for lecturers, especially those in charge of public service management, need to provide technical practicum skills so that students and female students have provisions and skills that support their work after graduating from college.